Students’ Perceptions of the Role of Guidance and Counseling Teachers in Improving Student Discipline at SMPN 22 Jambi City - Tesalonika Hasugian; K.A. Rahman; Rully Andi Yaksa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Creating students with strong character requires a conducive, comfortable, and dynamic learning environment supported by the consistent enforcement of school rules through disciplinary practices. Although the role of school counselors in enhancing student discipline at SMPN 22 Jambi City has been implemented, it has not yet reached its full potential. This study aims to describe students’ perceptions of the role of school counselors in improving student discipline at SMPN 22 Jambi City, viewed from three aspects: stimulus reception, understanding, and evaluation. The research employed a quantitative method with a descriptive approach. Data were collected from 224 students of SMPN 22 Jambi City who were selected as research participants. The data were obtained through a questionnaire based on a Likert scale and analyzed using percentage calculations. The findings indicate that, in general, students’ perceptions of the role of school counselors in enhancing student discipline fall within the good category, with an overall percentage score of 82%. Based on the research indicators, the percentage scores for stimulus reception, understanding, and evaluation were 80%, 82%, and 82%, respectively, all of which are categorized as good. These findings suggest that students positively perceive the contribution of school counselors in fostering discipline, particularly through guidance, support, and counseling services that encourage compliance with school regulations and the development of responsible behavior.